2010
DOI: 10.1002/jbm.a.32794
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineered hyaluronic acid elicited a nonantigenic T cell activation: Implications from cosmetic medicine and surgery to nanomedicine

Abstract: Hyaluronan is known to act as a filling material of extracellular matrices and as an adhesive substrate for cellular migration. Consequently, it is widely used in aesthetic medicine and surgery, and it would be expected to be used in nanomedicine. Previous clinical case reports associated hyaluronic acid implants to delayed immune-mediated adverse effects. A series of experiments to evaluate immune cell activation supported by this dermal filler and nanomedical biomaterial were performed. The study comprised a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 48 publications
2
20
1
Order By: Relevance
“…In spite of that, antibiotics are used as a treatment of this kind of medical complications though the role of antibiotics either as anti-inflammatory or bactericidal drugs is disputable. Although we were not able to demonstrate their anti-inflammatory effect in two previous in vitro studies [21,22], other authors obtained different results. Webster et al [34], in an elegant study, showed that tetracyclines and ciprofloxacin dose-dependently inhibited granuloma formation in vitro.…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…In spite of that, antibiotics are used as a treatment of this kind of medical complications though the role of antibiotics either as anti-inflammatory or bactericidal drugs is disputable. Although we were not able to demonstrate their anti-inflammatory effect in two previous in vitro studies [21,22], other authors obtained different results. Webster et al [34], in an elegant study, showed that tetracyclines and ciprofloxacin dose-dependently inhibited granuloma formation in vitro.…”
Section: Discussioncontrasting
confidence: 91%
“…Our data partially agree with our clinical series, wherein bacteria were recovered in a few cases, and the response to antibiotics was unfavorable [10,16,18]. In other experiments, we did not find increased lymphokine production, except for mainly IFN-γ and IL-2, when human peripheral blood mononuclear cells were cultured with biomaterials in combination with bacterial lipopolysaccharide [21,22]. …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…12 With regard to the effect of hyaluronic acid on inflammatory mediators, immune cells, and oxidative stress, it has been observed that hyaluronic acid produces a low-grade inflammatory response when it stimulates peripheral blood mononuclear cells. 13 The same study also showed a slight increase in the production of interferon-γ and higher expression of CD25, CD69, and CD71 in phytohemagglutininstimulated peripheral blood mononuclear cells from patients who underwent hyaluronic acid filler injections and displayed adverse effects.…”
Section: Hyaluronic Acid and Nanomedicinementioning
confidence: 79%